Contribution of fish to food and nutrition security in Southern Africa: challenges and opportunities in fish production - Maulu, Sahya; Musuka, Confred Godfrey; Molefe, Montshwari; Ngoepe, Tlou Kevin; Gabriel, Ndakalimwe Naftal; Mphande, Joseph; Phiri, Msumenji; Muhala, Valdemiro; Macuiane, Messias Alfredo; Ndebele-Murisa, Mzime Regina; Hasimuna, Oliver Jolezya; Bokhutlo, Thethela; et al. (Frontiers in Nutrition, 2024)
This study investigated the role of fish in addressing food and nutrition security challenges in Southern Africa, focusing on ten countries including Angola, Zambia, Malawi, Mozambique, Namibia, Botswana, Zimbabwe, Lesotho, Eswatini, and South Africa. It examined the current state of food and nutrition security, fish production, and fish consumption patterns. Additionally, the study investigated the challenges and opportunities to enhance fish production in these countries thereby enhancing food and nutrition security. The findings revealed persistent challenges such as a high prevalence of food insecurity and malnutrition throughout the region. Fish production is hindered by overexploitation of fishery resources, inadequate fisheries management, susceptibility to climate-related shocks, limited investments in aquaculture, and inadequate access to input supplies such as quality fish seed and feed. Despite these obstacles, opportunities exist to promote sustainable fish production to enhance food security and nutrition. Countries endowed with extensive coastlines and inland waters exhibit significant potential for fishery development, while landlocked nations are increasingly exploring aquaculture as a viable solution. Addressing the challenges in fish production and capitalizing on opportunities requires comprehensive governance, technological innovation, policy interventions, and investment to ensure the sustainability and resilience of the fisheries and aquaculture industries in the region.